Assistance to black people in the Juquery asylum from 1898 to 1930 - Amanda Carolina Franciscatto Avezani; João Fernando Marcolan (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To reveal the assistance provided to black individuals hospitalized at the Juquery Asylum from 1898 to 1930, having considered the social context and the hegemony of medical knowledge of the time. METHODS Exploratory-descriptive, qualitative study, documentary analysis, in medical records of black individuals hospitalized at the Juquery Asylum from 1898 to 1930. The time frame encompassed specific institutional directions as well as the historical, political, economic, and social context experienced by the black population. Held at the archive of the historical and cultural heritage of the Juquery Hospital Complex, between July and December 2019. We used an instrument with questions related to sociodemographic data, date and anamnesis of entry, physical and psychological examination, diagnostic hypothesis, treatments performed, complications, outcome, and motive. The analysis was carried out according to stages of documentary analysis and was based on psychiatric theoretical references of the period. RESULT All medical records of the period were read (approximately 6,300), of which about 1,400 were of black individuals. Of these medical records, 457 were included, 140 of women and 317 of men, which were considered to have significant information for the study's objectives. Most of the participants had long-term hospitalizations, whose motive did not seem to be linked to the possibility of cure or social reintegration, but rather to segregation. From the diagnoses described, the impression is that these subjects composed a niche with immutable, permanent conditions, not amenable to therapeutics that would allow their return to society, exemplified by degeneration. A significant amount of the medical records do not contain data on treatments, which reinforces the hypothesis that they were kept hospitalized not for the purpose of care, but as a deposit of incurability; when they do bring data, we observe willful empiricism of the physician. Half of the medical records describe the outcomes of hospitalized people and indicate very high records of deaths, followed by referrals to other hospitalization institutions to prolong confinement. CONCLUSIONS Internees suffered from isolation and assistance focused on state policy allied to science, especially psychiatry, to legitimize exclusion of the socially undesirable.